A novel stabilized carbon-coated nZVI as heterogeneous persulfate catalyst for enhanced degradation of 4-chlorophenol. (May 2020) - Li, Song; Tang, Jingchun; Liu, Qinglong; Liu, Xiaomei; Gao, Bin
Graphic abstract: Highlights: Spherical carbon coated nZVI composite was developed by two-step method. The Fe 0 in the composite was stable even in ambient air condition. Carbon coated nZVI can efficiently degrade 4-CP by activating PS. Carbon coated nZVI can use dissolved oxygen to form hydroxyl radicals. Abstract: Nano zero-valent iron (nZVI) and its composite materials have been extensively studied in the field of environmental remediation. However, the oxidation and agglomeration of nZVI limits the large-scale application of nZVI in environmental remediation. This study developed a two-step method to prepare stable carbon-coated nZVI (Fe 0 @C) which combined hydrothermal carbonization and carbothermal reduction methods and used glucose and iron oxide (Fe3 O4 ) as precursors. When the carbothermal reduction temperature was 700 °C and the elemental molar ratio of carbon to iron was 22:1, stable Fe 0 @C can be generated. The nZVI particles are encapsulated by mesoporous carbon and embedded in the carbon spheres. The unique structure of carbon coating not only inhibits the agglomeration of nZVI, but also makes nZVI stable in air for more than 120 days. Not only that, the as-synthesized Fe 0 @C exhibited high catalytic activity toward the degradation of 4-chlorophenol (4-CP) by activating persulfate. Different from conventional nZVI catalysts in generation of sulfate radicals, Fe 0 @C selectively induced hydroxyl radicals for 4-CP degradation. Moreover, Fe 0 @C has been shown to efficiently degrade 4-CP by using the dissolved oxygen in water to form hydroxyl radicals. This study not only provides a simple, green method for the preparation of stabilized nZVI, but also provides the possibility of large-scale application of nZVI in the field of environmental remediation.